Computed Tomography Protocol Optimisation for Peadiatric Head Trauma: Radiation Dose and Image Quality Assessment - Anaafi, E. (University of Ghana, 2020)
Objectives: To optimize the radiation dose and assess the image quality for a set of protocols, by evaluating noise, contrast to noise ratio, modulation transfer function and noise power spectrum. Statement of Problem and Justification: Children are sometimes examined with Computed Tomography protocols designed for adults, leading to radiation dose which is higher than necessary. And this can result in radiation induced cancer. Lack of optimisation could lead to image quality higher than what is needed for diagnostic outcome or value of the procedure with associated high dose to patient. Optimising the protocols for paediatric head trauma CT imaging will reduce radiation dose. Methodology: Somaton Sensation 64 was used to scan the head of an anthropomorphic phantom with a set of protocols. ImageJ software was used to analyse the paediatric head image from the scanner. IMPACTSCAN dosimeter software was used to evaluate the radiation dose to the various organs in the head. MATLAB was used to analyse the Modulation Transfer Function and the Noise Power Spectrum. Results: The estimated Computed Tomography Dose Index volume (CTDIvol) increased with increasing tube current and tube voltage. The high pitch 0.9 gave a lower dose than the 0.5 pitch. Eye lens received the highest radiation dose (39.2 mGy) whiles the thyroid received the least radiation dose (13.7 mGy). There was an increase in noise (62.46) when the H60 kernel was used and a lower noise (8.829) was noticed when the H30 kernel was used. Conclusion: The results obtained in this work showed that the H30 kernel (smooth kernel) gave higher values for noise and CNR than the H60 (sharp kernel) which values were also high for the MTF and N
MPhil. Medical Physics
Keywords: Radiation; Computed Tomography imaging; Radiation dose